The comparative agendas project in Latin America: data and coding - Bevan, Shaun (2020)
This paper introduces the Comparative Agendas Project system of coding as well as a wealth of gathered and in process data from Latin America using this established and reliable system for capturing policy attention comparatively and over time. While this is not the first introduction of the coding system, it is the first introduction aimed at Latin America and a new type of political system beyond North American and European democracies. First, we present an overview of the Comparative Agendas Project (CAP) and the Master Codebook used to create comparative policy attention data across countries, over time, and between agendas. These details of CAP are discussed for Latin America in general and for Brazil, Colombia and Ecuador, countries that recently started to gather data using these coding.